Biomaterials and Oxygen Join Forces to Shape the Immune Response and Boost COVID‐19 Vaccines (Adv. Sci. 18/2021). Issue 18 (22nd September 2021) - Colombani, Thibault; Eggermont, Loek J.; Rogers, Zachary J.; McKay, Lindsay G. A.; Avena, Laura E.; Johnson, Rebecca I.; Storm, Nadia; Griffiths, Anthony; Bencherif, Sidi A.
Abstract : COVID‐19 Vaccines In article number 2100316 by Sidi A. Bencherif and co‐workers, it is demonstrated that advanced biomaterials can be leveraged to boost the effectiveness of SARS‐CoV‐2 protein subunit vaccines. Illustration depicting a subcutaneously injected oxygen‐releasing cryogel‐based COVID‐19 vaccine boosting the immune response, leading to a sustained production of highly effective neutralizing antibodies against SARS‐CoV‐2.